Treatment Profile and Etiology of Neonatal Jaundice in Newborn admitted in a tertiary care Centre of Nepal - Tamang, Poonam Bodh; Shrestha, Sabina; Lama, Lopsang; Dhungel, Amrit; Pandey, Sikha (Nepal Medical College Journal, 2025)
Neonatal jaundice is a yellowish discoloration of sclera and skin in a newborn baby due to increase bilirubin levels. Complication may include neonatal seizures, cerebral palsy (CP) or kernicterus. Cause of jaundice could be physiological or pathological but the need of treatment depends on serum bilirubin levels, postnatal age of baby and the underlying cause. This was a hospital based retrospective cross-sectional study of neonates admitted at Nepal Medical College Teaching Hospital during the period of January 2022 to Dec 2023. A total of 4,113 deliveries was conducted during the study period. Out of them, a total 1,031 newborns were admitted out of which 157 neonates (15.22%) had significant hyperbilirubinemia. Among them, 53.5% were male and 46.5% were female babies. Regarding the gestational age, 32 (20.38%) babies were preterm and 125 (79.62%) were full term. Common causes of hyperbilirubinemia were physiological jaundice 79 (50.32%) followed by sepsis 27 (17.20%), prematurity 22 (14.01%), infant of diabetic mother 16 (10.20%), birth asphyxia 3 (1.91%), 5 (3.2%) of intrauterine growth restriction cases, 4 (2.54%) and 1 (0.63%) were due to blood group (ABO and Rh) incompatibility, respectively. Phototherapy was given to 100.0% (157) of the babies. None of the case required exchange transfusion. All babies were discharged after treatment as general condition of babies were good.